Synthesis, Biological Properties and Comparative Molecular Docking Evaluation Studies of 1,3 and 1,4 Bis-Thiourea Derivatives as Potential Antimicrobial Resistant Agents - Wan Sharifatun Handayani, Wan Zullkiplee; Ferlicia, Rasin; Ainaa Nadiah, Abd Halim; Nur Arif, Mortadza; Noratikah, Ramli; Nur Izma Hani, Hani; Zainab, Ngaini (IJCRR, 2021)
Introduction: Thiourea is one of the promising class of compounds that possess various pharmacological activity including antibacterial properties. Objective: The rise of microbial resistant drugs has triggered an alarming response among researchers to developed new drugs with effective biological properties. The position of substituents and active pharmacophores play an important role in designing a lead compound with effective biological properties. Methods: In this study, two series of 1,3-bis-thiourea derivatives (3a-l) and 1,4 bis-thiourea derivatives (4a-l) were synthesised from the reaction of isophthaloyl diisothiocyanate intermediates with halogenated amines. Results: The comparative studies of antibacterial properties of 3a-l and 4a-l against the growth of E. coli showed the minimum inhibition of 3g (7mm inhibition) and 4g (18mm inhibition) compared to standard drug ampicillin (16mm inhibition). Molecular docking evaluation against E. coli DNA gyrase B showed strong binding interaction of 4g with binding affinity -6.7 kcal/mol and more hydrogen bond compared to 3g with binding affinity -6.4 kcal/mol). Conclusion: The study is significant in drug design in particular for the development of potential drugs with antimicrobial resistant properties.